De-framing the Indigenous Body. Ethnography, Landscape and Cultural Belonging in the Art of Pia Arke - Thisted, Kirsten (Nordlit, 2012)
The article presents the Greenlandic-Danish artist Pia Arke (1958-2007) and gives readings of various of her artworks, arguing that they attempt to negotiate a postcolonial condition. Arke was fascinated by the male European explorers and their fascination with the Arctic landscape, the Inuit and, not the least, the Inuit women. "Arctic Hysteria" is one of the main metaphors she used to describe this fascination - giving a whole new meaning to this concept invented by explorers and scientists to describe a special kind of pathology by which the inhabitants of the Arctic were classified and distinguished from other people. Where so many male intellectuals have responded to the European representations with resentment and anger, Arke chooses curiosity as her main approach. What did these men see? What made them see in this way? What did the women feel? How does it feel to take upon oneself this subject position of the cultural and sexual "Other"? Thus, instead of repeating the dichotomizing constructions, as is often the outcome of "Anti-Orientalist" or "Anti-Othering" studies, Arke re-lives and thereby out-lives and deconstructs the colonial representations, leaving the stage open for new images and encounters. Arke thus addresses some of the key problems in the discussion of representation, and her work becomes an important critique not only of the colonial representations itself, but of the way in which the postcolonial response has dealt with these issues, trying to bring us further and beyond.